Pag-unlad tatlong taon pabalik, limang taon paharap - Aguilar, Mila D. (Pinoy Tok, 1989)
Traces the Philippine socio-economic development, three years before and five years after 1989, from the vantage point of experts, government officials, businessmen, and ordinary consumers and housewives.